2023
DOI: 10.1186/s12880-023-01005-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of advanced diffusion models from diffusion weighted imaging in a large cohort study of breast lesions

Abstract: Background To evaluate multiple parameters in multiple b-value diffusion-weighted imaging (DWI) in characterizing breast lesions and predicting prognostic factors and molecular subtypes. Methods In total, 504 patients who underwent 3-T magnetic resonance imaging (MRI) with T1-weighted dynamic contrast-enhanced (DCE) sequences, T2-weighted sequences and multiple b-value (7 values, from 0 to 3000 s/mm2) DWI were recruited. The average values of 13 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(47 reference statements)
0
0
1
Order By: Relevance
“…This may be related to the vigorous cell proliferation, increased nuclear-cytoplasmic ratio, and decreased intercellular and intracellular space in malignant lesions, which highly refrains water molecule diffusion. Besides, we found that the AUC of Dt value in distinguishing malignant tumors from benign lesions in our study was higher compared to those reported by Ji et al and Jin et al [ 31 , 32 ]. We hypothesized that this discrepancy might be attributed to factors such as the relatively small number of lesions and the 2D delineation of the region of interest (ROI) in their research.…”
Section: Discussioncontrasting
confidence: 82%
“…This may be related to the vigorous cell proliferation, increased nuclear-cytoplasmic ratio, and decreased intercellular and intracellular space in malignant lesions, which highly refrains water molecule diffusion. Besides, we found that the AUC of Dt value in distinguishing malignant tumors from benign lesions in our study was higher compared to those reported by Ji et al and Jin et al [ 31 , 32 ]. We hypothesized that this discrepancy might be attributed to factors such as the relatively small number of lesions and the 2D delineation of the region of interest (ROI) in their research.…”
Section: Discussioncontrasting
confidence: 82%